2019
DOI: 10.1037/cou0000295
|View full text |Cite
|
Sign up to set email alerts
|

Toward a nuanced understanding of nondisclosure in psychotherapy supervision.

Abstract: Previous research indicates that trainees often withhold important information related to their clients' progress and their reactions to supervision. Moreover, factors associated with the occurrence of supervisee nondisclosure (SND) are not well established. As one of the few studies to compare clinically related with supervision-related nondisclosure, we tested the relation of these two dimensions of the construct, as measured by Siembor and Ellis's (2012) Supervisee Nondisclosure Scales, to three important p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
57
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(68 citation statements)
references
References 31 publications
7
57
4
Order By: Relevance
“…Indeed, Mehr et al (2010) and Ladany et al (1996) found that 38% and 90% of supervisees, respectively, did not disclose their negative reactions to their supervisors, and 44% withheld clinical mistakes (Ladany et al, 1996). Like others (Gibson et al, 2019;Jakob et al, 2014;Siembor & Ellis, 2012), (a) supervision-related nondisclosures were the most frequent type of SND here, but only 23% of participants withheld this information from their supervisors, and 29% indicated that it was not applicable, and (b) nearly half of our participants reported disclosing fully their clinical mistakes in supervision-only 1.4% decided not to disclose this information. The divergences are intriguing.…”
Section: Major Findingsmentioning
confidence: 95%
See 1 more Smart Citation
“…Indeed, Mehr et al (2010) and Ladany et al (1996) found that 38% and 90% of supervisees, respectively, did not disclose their negative reactions to their supervisors, and 44% withheld clinical mistakes (Ladany et al, 1996). Like others (Gibson et al, 2019;Jakob et al, 2014;Siembor & Ellis, 2012), (a) supervision-related nondisclosures were the most frequent type of SND here, but only 23% of participants withheld this information from their supervisors, and 29% indicated that it was not applicable, and (b) nearly half of our participants reported disclosing fully their clinical mistakes in supervision-only 1.4% decided not to disclose this information. The divergences are intriguing.…”
Section: Major Findingsmentioning
confidence: 95%
“…mistakes; CRND) and supervision-related nondisclosures (e.g., negative reactions to one's supervisor; SRND; Gibson, Ellis, & Friedlander, 2019;Jakob, Weck, Höfling, Richtberg, & Bohus, 2014;Webb & Wheeler, 1998;Yourman & Farber, 1996), SND is most often conceptualized unidimensionally (e.g., Mehr, Ladany, & Caskie, 2015). It is not surprising then that the salient constructs predictive of multidimensional SND have yet to be identified and tested.…”
mentioning
confidence: 99%
“…They reported that the supervisees feared being considered inadequate practitioners. Likewise, other researchers have found that common reasons why supervisees avoid disclosing information include: supervisees' concerns about how they would be seen and evaluated by the supervisor (Hess et al., 2008), the supervisees' predominantly negative recollection of supervision experience (Gibson et al., 2019) and feelings of shame (Yourman & Farber, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Further factors include uncomfortable feelings such as embarrassment, shame, vulnerability and self‐doubt (Hess et al, 2008; Ladany et al, 1996). Experiences of a weak supervisory alliance are yet another commonly reported reason behind supervisee nondisclosures (Gibson, Ellis, & Friedlander, 2019; Hess et al, 2008; Ladany et al, 1996; Mehr et al, 2010).…”
Section: Introductionmentioning
confidence: 99%